Optimization Study in Biodiesel Production via Response Surface Methodology Using Dolomite as a Heterogeneous Catalyst. (30th November 2014) - Santos, Regina C. R.; Vieira, Rômulo B.; Valentini, Antoninho
Abstract : A carbonate mineral, dolomite, was used as a heterogeneous catalyst to produce methyl-esters from soybean oil. The samples were analyzed by XRF, TGA, XRD, TPD-CO2, and SEM. The calcination of dolomite at 800°C/1 h resulted in a highly active mixed metal oxides. In addition, the influence of the reaction variables such as the temperature, catalyst amount, and methanol/soybean oil molar ratio in methyl-ester production was optimized by the application of a central composite design in conjunction with the response surface methodology (RSM). The XRF analysis is carried out after the reuses procedure which shows that the deactivation process is mainly due to the selective calcium leaching. Overall, the calcined dolomite exhibited high catalytic activity at moderate operating conditions for biodiesel production.